Non-volatile logic gates based on planar Hall effect in magnetic films with two in-plane easy axes - Sangyeop Lee; Seul-Ki Bac; Seonghoon Choi; Hakjoon Lee; Taehee Yoo; Sanghoon Lee; Xinyu Liu; M. Dobrowolska; Jacek K. Furdyna (Scientific Reports, 2017)
Abstract We discuss the use of planar Hall effect (PHE) in a ferromagnetic GaMnAs film with two in-plane easy axes as a means for achieving novel logic functionalities. We show that the switching of magnetization between the easy axes in a GaMnAs film depends strongly on the magnitude of the current flowing through the film due to thermal effects that modify its magnetic anisotropy. Planar Hall resistance in a GaMnAs film with two in-plane easy axes shows well-defined maxima and minima that can serve as two binary logic states. By choosing appropriate magnitudes of the input current for the GaMnAs Hall device, magnetic logic functions can then be achieved. Specifically, non-volatile logic functionalities such as AND, OR, NAND, and NOR gates can be obtained in such a device by selecting appropriate initial conditions. These results, involving a simple PHE device, hold promise for realizing programmable logic elements in magnetic electronics.